1997
DOI: 10.1002/(sici)1096-9861(19970908)385:4<599::aid-cne6>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neonatal capsaicin and infraorbital nerve section on whisker-related patterns in the rat trigeminal nucleus

Abstract: In the present study, we investigated the effect of neonatally administered capsaicin on whisker-related pattern formation in the rat trigeminal complex. Both normal whisker-related patterns of barrelettes and the modified patterns seen after neonatal section of the infraorbital nerve were assessed. Capsaicin caused no change in the pattern or size of cytochrome oxidase (CO) barrelettes in the principal trigeminal nucleus (Vp) or trigeminal nucleus interpolaris (Vi) or caudalis (Vc). Injections of horseradish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 92 publications
1
3
0
Order By: Relevance
“…In this nucleus, as in Pr5 or Sp5ip, sets of primary afferents and clusters of neurons aggregate to form the vibrissa‐related patterns known as barrelettes (Arvidsson, ; Belford and Killackey, ; Chiaia et al, ). In Sp5c these clusters distribute in laminae III–IV and spare laminae I–II (Waite and De Permentier, ), as did most of our Sp5c–Pr5 neurons. Early electrophysiological studies showed that laminae III and IV neurons receive predominantly non‐nociceptive inputs of Aβ fibers (Willis and Coggeshall, ) and are activated by vibrissae and/or guard hair deflection, whereas cells that responded best to nociceptive stimulation were located primarily in laminae I, II, and deep V (Renehan et al, ).…”
Section: Discussionsupporting
confidence: 65%
“…In this nucleus, as in Pr5 or Sp5ip, sets of primary afferents and clusters of neurons aggregate to form the vibrissa‐related patterns known as barrelettes (Arvidsson, ; Belford and Killackey, ; Chiaia et al, ). In Sp5c these clusters distribute in laminae III–IV and spare laminae I–II (Waite and De Permentier, ), as did most of our Sp5c–Pr5 neurons. Early electrophysiological studies showed that laminae III and IV neurons receive predominantly non‐nociceptive inputs of Aβ fibers (Willis and Coggeshall, ) and are activated by vibrissae and/or guard hair deflection, whereas cells that responded best to nociceptive stimulation were located primarily in laminae I, II, and deep V (Renehan et al, ).…”
Section: Discussionsupporting
confidence: 65%
“…The ION does innervate the nasal septum, but it primarily innervates cutaneous structures, such as the skin of the side of the nose and lower eyelid, and lower and upper lip (Shankland, 2001b ; Gray et al, 2016 ). Furthermore, the ION provides the major sensory innervation of the mystacial vibrissae of rodents (Vincent, 1913 ; Dykes, 1975 ; Jacquin et al, 1984 ; Rice et al, 1993 ; Waite and de Permentier, 1997 ; Maklad et al, 2004 ). Injection of WGA into the main trunk of the ION within the orbit labeled the superficial laminae of MDH in a fashion similar to WGA labeling of individual vibrissae (Arvidsson, 1982 ; Nomura et al, 1986 ; Arvidsson and Rice, 1991 ) or the palpebral conjunctiva (Panneton et al, 2010c ).…”
Section: Discussionmentioning
confidence: 99%
“…A systemic administration of capsaicin to neonatal animals caused attenuation of the nociceptive reflex against noxious chemical and thermal stimuli in their postnatal stage by an elimination of unmyelinated afferent fibers (6,10,13,16,37). However, animals with neonatal capsaicin treatment displayed a re-appearance of SP-immunoreaction in the dorsal horn during the postnatal period despite the continuous suppression of nocifensive responses (12).…”
Section: Animals and Neonatal Capsaicin Treatmentmentioning
confidence: 99%